2020
DOI: 10.1001/jamapsychiatry.2019.2998
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of the Association Between Goal-Directed Planning and Self-reported Compulsivity vs Obsessive-Compulsive Disorder Diagnosis

Abstract: IMPORTANCE Dimensional definitions of transdiagnostic mental health problems have been suggested as an alternative to categorical diagnoses, having the advantage of capturing heterogeneity within diagnostic categories and similarity across them and bridging more naturally psychological and neural substrates. OBJECTIVE To examine whether a self-reported compulsivity dimension has a stronger association with goal-directed and related higher-order cognitive deficits compared with a diagnosis of obsessive-compulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
58
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 65 publications
11
58
2
Order By: Relevance
“…In addition, the expected associations between the COHS subscales and clinical scores indicate good external consistency. Indeed, as in previous studies (Ersche et al, 2017 , 2019 ), we found an association between a compulsivity score (Zermatten et al, 2006 ) and the two COHS subscales, thus confirming the past empirical results showing individuals with a compulsive tendency relied strongly on a habitual mode of action (Voon et al, 2015 ; Gillan et al, 2016 , 2019 ). Additionally, we found that the impulsivity was inversely proportional to routine tendencies, which is consistent with the proposition that goal-striving individuals managing their behaviors with consideration for the consequences of their actions in mind are less inclined to allow environmental stimuli to take over control, a phenomenon related to impulsivity (Lanza and Drabick, 2011 ; Ersche et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the expected associations between the COHS subscales and clinical scores indicate good external consistency. Indeed, as in previous studies (Ersche et al, 2017 , 2019 ), we found an association between a compulsivity score (Zermatten et al, 2006 ) and the two COHS subscales, thus confirming the past empirical results showing individuals with a compulsive tendency relied strongly on a habitual mode of action (Voon et al, 2015 ; Gillan et al, 2016 , 2019 ). Additionally, we found that the impulsivity was inversely proportional to routine tendencies, which is consistent with the proposition that goal-striving individuals managing their behaviors with consideration for the consequences of their actions in mind are less inclined to allow environmental stimuli to take over control, a phenomenon related to impulsivity (Lanza and Drabick, 2011 ; Ersche et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…The same applies to goal-directed planning, which is both deficient in patients tested in-person 9 and correlated with OCD symptoms in the general population tested online 17,26 . Notably, recent work in a patient sample even found that goal-directed deficits were more strongly associated with the compulsivity dimension than OCD diagnosis status 27 . As such, there is no reason to suspect these findings are not applicable to patients.…”
Section: Discussionmentioning
confidence: 95%
“…Whether these findings generalise to other aspects of mental health is not yet known. Prior work suggests that transdiagnostic approached might be ultimately more powerful in the context of linking cognitive changes to mental health phenomena, and so it may also prove true here [60,61]. We may find…”
Section: Resultsmentioning
confidence: 80%